Influence of Religiosity on Youths' Attitudes Towards People with Disabilities in the United Arab Emirates. - Hammad, Hamza; Elbarazi, Iffat; Bendak, Malik; Obaideen, Khaled; Amanatullah, Asma; Khan, Bibi Sara Badshah; Ismail, Leila; Kieu, Alex; AB Khan, Moien (Journal of Religion & Health, 2024)
This cross-sectional survey investigates the influence of youths' religiosity on their attitude towards people with disabilities. The Muslim religiosity questionnaire and multidimensional attitudes scale towards persons with disabilities were used to survey 733 youths from the federal university in the United Arab Emirates. The results indicated that the youths were religious and had positive attitudes towards people with disabilities. An increase in religiosity is associated with a positive attitude towards disability, and both religiosity and total family income positively impacted the attitude towards people with disabilities. Reducing inequalities by including persons with disabilities is one of the UN 2030 Agenda for Sustainable Development objectives. Policies should aim to enhance curriculum, improvise public guidelines and partner with associated faith-based leaders to build an inclusive society for people with disabilities, thus helping to achieve sustainable development goals.